After All : a Hanover Falls Novel - Raney, Deborah (Nashville, Tenn. : Howard Books, 2012)
"Featuring her trademark warm, friendly style, the final novel in bestselling and award-winning Deborah Raney's Hanover Falls series offers plenty of romance and mystery as three people find hope, forgiveness, and love in unexpected places. Eighteen months after the tragic Grove Street Fire took the life of her husband and four other heroic firefighters, Susan Marlowe thinks she's finally beginning to heal. But then she discovers that David carried a secret to his grave--a secret that changes everything she thought about their marriage. For the sake of their sons, can Susan forgive the unforgivable? Andrea Morley lost her closest friend in the fire. But she has no right to mourn him. Instead, she must forever grieve in silence--for someone else's husband. Peter Brennan carries the weight of the world on his shoulders. As Hanover Falls fire chief, he was responsible for the brave firefighters who lost their lives that awful November night. Can he ever shake the feeling that he could have somehow prevented the tragedy? And now it seems he might find comfort in the arms of the woman he least expected"--
Keywords: Fire fighters -- Fiction; FICTION / Christian / Romance; FICTION / Christian / Suspense; FICTION / Christian / General; Christian fiction; Love stories